Neuropeptides SP and CGRP Diminish the Moraxella catarrhalis Outer Membrane Vesicle- (OMV-) Triggered Inflammatory Response of Human A549 Epithelial Cells and Neutrophils - Daria Augustyniak; Justyna Roszkowiak; Izabela Wiśniewska; Jacek Skała; Daiva Gorczyca; Zuzanna Drulis-Kawa (Mediators of Inflammation)
Neuropeptides such as substance P (SP) and calcitonin gene-related peptide (CGRP) play both pro- and anti-inflammatory activities and are produced during infection and inflammation. Moraxella catarrhalis is one of the leading infectious agents responsible for inflammatory exacerbation in chronic obstructive pulmonary disease (COPD). Since the airway inflammation in COPD is connected with activation of both epithelial cells and accumulated neutrophils, in this study we determined the in vitro effects of neuropeptides on the inflammatory potential of these cells in response to M. catarrhalis outer membrane vesicle (OMV) stimulant. The various OMV-mediated proinflammatory effects were demonstrated. Next, using hBD-2-pGL4[luc2] plasmid with luciferase reporter gene, SP and CGRP were shown to inhibit the IL-1β-dependent expression of potent neutrophil chemoattractant, hBD-2 defensin, in transfected A549 epithelial cells (type II alveolar cells) upon OMV stimulation. Both neuropeptides exerted antiapoptotic activity through rescuing a significant fraction of A549 cells from OMV-induced cell death and apoptosis. Finally, CGRP caused an impairment of specific but not azurophilic granule exocytosis from neutrophils as shown by evaluation of gelatinase-associated lipocalin (NGAL) or CD66b expression and elastase release, respectively. Concluding, these findings suggest that SP and CGRP mediate the dampening of proinflammatory action triggered by M. catarrhalis OMVs towards cells engaged in lung inflammation in vitro.